The dictionary of cliches - Rogers, James T. (New York, N.Y. : Facts on File Publications, 1985)
"Over 2,000 common or amusing cliches, their meanings and origins."
Includes index.
Keywords: v; English language -- Usage -- Dictionaries; Figures of speech; Anglais (Langue) -- Mots et locutions; Anglais (Langue) -- Usage -- Dictionnaires; Proverbes anglais; Phraseologie; Sprichwort; Englisch; 2; English language -- Usage; Figures of speech; a; English language -- Usage -- Dictionaries; Figures of speech; 2; Dictionaries